A escolarização da comunidade nipo-brasileira de Registro (1913-1963) - Omuro, Selma de Araujo Torres (2015)
This research is about the Japanese-Brazilian community schooling in the colonial core of the city of Registro-SP, between 1913 and 1963. This educational experience has developed through an important period of Brazilian education during the implementation process of the policy of expansion, centralization and nationalization of education. It analyzes contradictory versions about the role that Japanese schools have performed in that period. The research aims to: 1) understand the organization, functioning and objectives of Japanese schools; 2) analyze the context and the impact of closing these schools to the Japanese community, 3) contribute to the discussions concerning to the cultural differences that characterize Brazilian society. It started from the hypothesis that the schooling of Japanese immigrants was a unique process that can not be reduced to stereotypical models that classified it as a center of the dissemination of Japanese imperialism in Brazil, or as a center of pure assimilation to a homogeneous national culture. It is also believed that the nationalization of education did not occur as smoothly as reported by the official versions of the process. The research drew on diverse sources: official documents of the State of São Paulo public education (Anuário de Ensino do Estado de São Paulo - Education Yearbooks of the State of São Paulo) photographs and documents from oral and written memory of the Japanese-Brazilian community of the city of Registro. The treatment of the sources relied on the theoretical and methodological framework of authors like Marson (1994), Kossoy (2001), Leite (2001), Alberti (2005), Pollak (1989), E.P. Thompson (1981) Certeau (2012). The realized studies allowed us to imply that education of the Japanese-Brazilian community in Registro was a process marked by diverse cultural influences and the existence of conflicts that were minimized by the "official history" of immigration in the studied city. It was found that Japanese-Brazilians were eventually able to integrate successfully into the national school, but managed to preserve their culture s traits in the studied location